Zinc-based battery, preparation method thereof and electric equipment

By applying an amphoteric hydroxide coating to the positive electrode sheet and/or the separator surface of the zinc-based battery, the problem of hydrogen evolution reaction during charging is solved, and the cycle stability and electrochemical performance of the battery are improved.

CN119812509AActive Publication Date: 2025-04-11BYD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411599028.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-04-11
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Zinc-based batteries are prone to hydrogen evolution reactions when charging, resulting in the generation of by-products and affecting the cycle stability and electrochemical performance of the battery.

Method used

The positive electrode sheet and/or the separator surface of the zinc-based battery are coated with an amphoteric hydroxide coating, which has a pH buffering effect and inhibits water activity, and avoids the formation of hydrogen evolution and by-products.

Benefits of technology

It improves the electrolyte stability of zinc-based batteries, enhances cycle stability and electrochemical performance, and reduces the possibility of battery out of control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128241590000091
    Figure BDA0005128241590000091
  • Figure BDA0005128241590000101
    Figure BDA0005128241590000101
  • Figure HDA0005128241740000011
    Figure HDA0005128241740000011
Patent Text Reader

Abstract

The invention discloses a zinc-based battery, a preparation method thereof and electric equipment. The zinc-based battery comprises a positive pole piece, a diaphragm and a negative pole piece, at least part of the surface of the positive pole piece and / or at least part of the surface of the diaphragm are / is provided with a coating, and the coating comprises amphoteric hydroxide. The zinc-based battery is high in cycling stability and excellent in electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to zinc-based batteries, preparation methods thereof, and electrical equipment thereof. Background Art

[0002] As a device for converting electrical energy into chemical energy, batteries have been widely used in daily life and work, and research on aqueous zinc-based batteries has gradually emerged in recent years. Zinc-based batteries use zinc as the negative electrode active material, and have the advantages of low redox potential, high theoretical capacity, high safety, and high metal resource abundance. They have many advantages such as low cost, high energy density, safety and environmental protection, and a wide range of material sources. They match the current market demand and are currently a research hotspot in academia and industry.

[0003] At present, zinc-based batteries usually use water as the electrolyte solvent. When the battery is charged, hydrogen evolution reaction is prone to occur. The reduction of hydrogen ions will induce the formation of byproducts, such as basic zinc sulfate. These byproducts will be deposited at the positive and negative electrodes at the same time, which can easily lead to poor contact between the active material and the electrolyte at the positive electrode, and uneven deposition sites at the negative electrode. The latter will also destroy the stability of subsequent deposition and gradually form dendrites, which may pierce the diaphragm and cause a short circuit, posing a challenge to the use of zinc-based batteries in real life. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a zinc-based battery and a preparation method and an electrical device thereof. The zinc-based battery of the present application has strong electrolyte stability, is not prone to hydrogen evolution and by-product generation, has strong cycle stability, and has good electrochemical performance.

[0005] The first aspect of the present application provides a zinc-based battery. According to an embodiment of the present application, the zinc-based battery comprises: a positive electrode sheet, a separator and a negative electrode sheet;

[0006] At least a portion of the surface of the positive electrode plate and / or at least a portion of the surface of the separator has a coating, and the coating includes an amphoteric hydroxide.

[0007] According to the zinc-based battery of the embodiment of the present application, at least part of the surface of the positive electrode sheet and / or the separator has a coating including an amphoteric hydroxide, and the amphoteric hydroxide has a pH buffering effect, so that the H at the electrode interface + or OH - The concentration can be effectively buffered when it changes instantaneously, avoiding the occurrence of hydrogen evolution and the generation of alkaline byproducts, thereby reducing the possibility of battery runaway. At the same time, amphoteric hydroxides have an inhibitory effect on water activity, thereby improving the stability of the electrolyte environment. As a result, the cycle stability and electrochemical performance of zinc-based batteries are improved overall.

[0008] According to the embodiments of the present application, the above-mentioned zinc-based battery also has the following additional technical features:

[0009] According to an embodiment of the present application, the amphoteric hydroxide includes at least one of hydroxides of boron, aluminum, silicon, zinc, gallium, germanium, arsenic, selenium, indium, tin, antimony, tellurium, lead, bismuth, manganese, polonium and astatine.

[0010] According to an embodiment of the present application, the amphoteric hydroxide includes at least one of Al(OH)3, Be(OH)2 and Zn(OH)2.

[0011] According to an embodiment of the present application, the mass proportion of the amphoteric hydroxide in the coating is 66% to 100%.

[0012] According to an embodiment of the present application, the coating further includes: at least one of a binder and an interface adsorbent.

[0013] According to an embodiment of the present application, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, styrene-acrylic acid and polyacrylic acid;

[0014] And / or, the interfacial adsorbent includes anionic surfactant and / or nonionic surfactant.

[0015] According to an embodiment of the present application, the anionic surfactant includes at least one of alkyl sulfates, sulfonates, fatty acids, fatty acid ester sulfates, carboxylic acid soap compounds and phosphate compounds;

[0016] And / or, the nonionic surfactant includes at least one of polyoxyethylene alkylphenol ether and polyoxyethylene fatty alcohol ether.

[0017] According to an embodiment of the present application, the coating comprises:

[0018] 60 to 100 parts by weight of amphoteric hydroxide;

[0019] 0 to 20 parts by weight of a binder;

[0020] 0 to 10 parts by weight of an interface adsorbent.

[0021] According to an embodiment of the present application, the thickness of the coating is 60 μm to 250 μm.

[0022] According to an embodiment of the present application, the zinc-based battery further includes: an electrolyte, wherein the electrolyte includes water.

[0023] According to an embodiment of the present application, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes at least one of a manganese-based material, a vanadium-based material, Prussian blue and the like, a halogen-based material, and an organic material.

[0024] The second aspect of the present application provides a method for preparing the zinc-based battery described in the first aspect. According to an embodiment of the present application, the method comprises:

[0025] Applying a coating slurry on at least a portion of the surface of the positive electrode sheet and / or the separator, and drying to form the coating;

[0026] Wherein, the coating slurry includes the amphoteric hydroxide.

[0027] According to an embodiment of the present application, the coating slurry further includes at least one of a binder and an interface adsorbent and a solvent.

[0028] According to an embodiment of the present application, the solvent includes at least one of N-methylpyrrolidone, N-dimethylformamide, and deionized water.

[0029] According to an embodiment of the present application, the solid content of the coating slurry is 30 mass % to 70 mass %.

[0030] The third aspect of the present application provides an electrical device. According to an embodiment of the present application, the electrical device comprises the zinc-based battery described in the first aspect or the zinc-based battery obtained by the method for preparing the zinc-based battery described in the second aspect.

[0031] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0033] Figure 1 A pH-cycle number measurement record diagram of one embodiment of the present application is shown;

[0034] Figure 2 A forward linear voltammetric scanning curve diagram of an embodiment of the present application is shown;

[0035] Figure 3 A negative linear voltammetric scanning curve diagram of an embodiment of the present application is shown. DETAILED DESCRIPTION

[0036] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0037] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0038] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this application.

[0039] In the present application, the terms "comprise" or "include" are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0040] Zinc-based batteries usually include positive electrode sheets, negative electrode sheets, electrolytes and separators. The electrolyte usually uses water as solvent, zinc salt as solute, and is combined with functional additives. The ions in the electrolyte exist in a solvated structure. During the reaction, they will lose active free water after reaching the electrode-electrolyte interface and dissociate a certain amount of H + and OH - When the battery is charged, a small amount of hydrogen evolution reaction will occur due to the similar reaction voltage, which poses a hidden danger to battery safety. At the same time, during operation, due to the existence of the above problems and the H generated by intercalation and conversion reactions, + Consumption makes OH at the positive and negative electrode interface - The concentration rises rapidly, and it is easy to form poorly conductive basic zinc sulfate. Basic zinc sulfate has a loose morphology and cannot provide the necessary function and protection for the negative electrode like the SEI layer of lithium batteries, causing the discharge capacity to decay in subsequent cycles and resulting in a decrease in energy density. Such byproducts will also lead to uneven deposition sites at the negative electrode, which can easily destroy the stability of subsequent deposition and gradually form dendrites, posing a risk of piercing the diaphragm and causing a short circuit, posing a challenge to the use of zinc-based batteries in real life.

[0041] In order to deal with the above problems, some solutions have been proposed. For example, the electrolyte is modified and pH buffering or water activity inhibition additives are introduced. The former is not effective at low concentrations due to slow mass transfer; and when the concentration is increased, such additives will challenge the stability of the negative electrode. The latter often requires higher concentrations to be effective, which will significantly increase costs and reduce the mass transfer efficiency of the electrolyte. These strategies are limited to laboratory preparation and are difficult to put into industrial production.

[0042] In view of this, the present application applies a coating on the surface of the positive electrode plate and / or the diaphragm of the zinc-based battery, wherein the coating contains amphoteric hydroxides, which can effectively improve the stability of the electrolyte, make hydrogen evolution and by-product generation less likely to occur, and improve the cycle stability and electrochemical performance of the battery.

[0043] The first aspect of the present application provides a zinc-based battery. According to an embodiment of the present application, the zinc-based battery comprises: a positive electrode sheet, a separator and a negative electrode sheet;

[0044] At least a portion of the surface of the positive electrode plate and / or at least a portion of the surface of the separator has a coating, and the coating includes an amphoteric hydroxide.

[0045] Amphoteric hydroxides can react with H + OH - Reaction, in H + and OH - When the concentration changes, the ion concentration can be balanced through reaction, which has a pH buffering effect. Using amphoteric hydroxide as the coating material can make the H at the electrode interface + or OH - The concentration is effectively buffered when it changes instantaneously, avoiding the occurrence of hydrogen evolution and the generation of alkaline byproducts, thereby reducing the possibility of battery runaway. At the same time, hydroxides have an inhibitory effect on water activity, thereby improving the stability of the electrolyte environment. In addition, compared with other types of compounds of amphoteric elements, amphoteric hydroxides are more stable and less prone to dehydration. Moreover, amphoteric hydroxides have not only ionic bonds, but also hydrogen bonds, and the OH of amphoteric hydroxides - The low electricity price weakens the interaction between anions and cations, so the relative density and hardness tend to decrease, making it more suitable for zinc-based battery systems. Therefore, a coating containing amphoteric hydroxides can improve the cycle stability and electrochemical performance of zinc-based batteries as a whole.

[0046] It should be noted that the coating can be provided on the positive electrode plate, on the diaphragm, or on both the positive electrode plate and the diaphragm. When the coating is provided on the positive electrode plate, its average discharge specific capacity will be slightly higher than when it is provided on the diaphragm. This is because the contact between the coating and the positive electrode is closer, which can shorten the electron or ion conduction path, thereby improving the electrochemical performance. When the coating is provided on the diaphragm, the stability is slightly improved because it can radiate to the negative electrode interface to a certain extent.

[0047] According to an embodiment of the present application, the amphoteric hydroxide includes at least one of the hydroxides of boron, aluminum, silicon, zinc, gallium, germanium, arsenic, selenium, indium, tin, antimony, tellurium, lead, bismuth, manganese, polonium and astatine. In some embodiments, the amphoteric hydroxide includes at least one of Al(OH)3, Be(OH)2 and Zn(OH)2. The above-mentioned amphoteric hydroxide can effectively buffer the pH value of the electrolyte, avoid inducing hydrogen evolution and generating alkaline by-products, and at the same time can inhibit water activity and further improve the stability of the electrolyte environment. As a result, the cycle stability and electrochemical performance of the zinc-based battery can be better improved.

[0048] According to an embodiment of the present application, the mass proportion of the amphoteric hydroxide in the coating is 66% to 100%, for example, it can be 66%, 70%, 75%, 80%, 85%, 90%, 95%, 99%, 100%. The amphoteric hydroxide has good adhesion and can be used as the only component of the coating to adhere to at least part of the surface of the positive electrode plate and / or the diaphragm, and is not easy to fall off. It can also be used as a partial component of the coating. The amphoteric hydroxide meets the above conditions and can more effectively buffer the pH value of the electrolyte, avoid inducing hydrogen evolution and generating alkaline by-products, and can inhibit water activity and further improve the stability of the electrolyte environment. As a result, the cycle stability and electrochemical performance of the zinc-based battery can be better improved.

[0049] According to an embodiment of the present application, the coating further includes: at least one of a binder and an interface adsorbent. The binder can enhance the adhesion between the coating and the positive electrode sheet and / or the separator, ensure the uniform distribution and long-term stability of the coating, and help improve the electronic conductivity and promote the electronic exchange between the active material in the coating and the electrode, thereby improving the overall electrochemical performance and cycle stability of the battery.

[0050] Since amphoteric hydroxides are hydrophobic and have low affinity with water-based electrolytes, poor contact between the coating and the electrolyte may occur, which is not conducive to the passage of substances (such as ions) in the electrolyte through the coating, thereby limiting the material transfer rate and slightly affecting the electrochemical performance of the battery. Interfacial adsorbents can improve the interaction between the coating and the electrolyte by increasing the hydrophilicity of the coating surface, thereby increasing the material transfer rate and battery performance, and helping to improve the stability and cycle life of the battery.

[0051] According to an embodiment of the present application, the binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), styrene-acrylic acid (SA) and polyacrylic acid (PAA). Thus, the adhesion between the coating and the positive electrode sheet and / or the separator can be further enhanced, ensuring the uniform distribution and long-term stability of the coating, and helping to further improve the electronic conductivity and promote the electronic exchange between the active material in the coating and the electrode, thereby better improving the overall electrochemical performance and cycle stability of the battery.

[0052] According to an embodiment of the present application, the interface adsorbent includes anionic surfactants and / or nonionic surfactants. Thus, the hydrophilicity of the coating surface can be further increased, and the interaction between the coating and the electrolyte can be improved, thereby better improving the material transfer rate and battery performance, and helping to improve the stability and cycle life of the battery.

[0053] According to an embodiment of the present application, the anionic surfactant includes at least one of alkyl sulfate, sulfonate, fatty acid, fatty acid ester sulfate, carboxylic acid soap compound and phosphate compound; and / or, the nonionic surfactant includes at least one of polyoxyethylene alkylphenol ether and polyoxyethylene fatty alcohol ether. In some embodiments, the sulfonate can be sodium dodecylbenzene sulfonate (SDBS). Thus, the hydrophilicity of the coating surface can be further increased, and the interaction between the coating and the electrolyte can be improved, thereby better improving the material transfer rate and battery performance, and helping to improve the stability and cycle life of the battery.

[0054] According to an embodiment of the present application, the coating comprises:

[0055] 60 to 100 parts by weight of amphoteric hydroxide, for example, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, 100 parts by weight;

[0056] 0 to 20 parts by weight of a binder, for example, 0, 1, 2, 3, 4, 5, 10, 15, or 20 parts by weight;

[0057] The amount of the interfacial adsorbent may be 0 to 10 parts by weight, for example, 0, 1, 2, 4, 5, 6, 8 or 10 parts by weight.

[0058] Amphoteric hydroxides, binders and interfacial adsorbents that meet the above conditions can effectively buffer the pH value of the electrolyte, avoid hydrogen evolution and the generation of alkaline byproducts, and inhibit water activity, further improving the stability of the electrolyte environment. In addition, the coating can stably adhere to the positive electrode sheet and / or the diaphragm, is not easy to fall off, has good affinity with the electrolyte, and is conducive to the transmission of electrons and ions. Thus, the overall electrochemical performance and cycle stability of the battery are better improved.

[0059] According to an embodiment of the present application, the thickness of the coating is 60 μm to 250 μm, for example, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 150 μm, 180 μm, 200 μm, 220 μm, 240 μm, 250 μm. Thus, the pH value of the electrolyte can be effectively buffered to avoid hydrogen precipitation and the generation of alkaline by-products, while suppressing water activity and further improving the stability of the electrolyte environment. Moreover, the electron and ion transmission efficiency is high, the battery internal resistance is low, it is not easy to have excessive volume expansion and contraction during the charge and discharge process, and the coating has strong mechanical stability.

[0060] According to an embodiment of the present application, the zinc-based battery further includes: an electrolyte, wherein the electrolyte includes water. The electrolyte also includes a solute, wherein the solute includes a zinc salt and a manganese salt, wherein the zinc salt includes one or more of ZnSO4, ZnCl2, Zn(NO3)2, Zn(H2PO4)2, ZnHPO4, Zn(CH3COO)2, Zn(ClO4)2, Zn(BF4)2, Zn(CF3SO3)2, and Zn(TFSI)2. The manganese salt includes one or more of MnSO4, MnCl2, Mn(NO3)2, Mn(H2PO4)2, MnHPO4, Mn(CH3COO)2, Mn(ClO4)2, Mn(BF4)2, Mn(CF3SO3)2, and Mn(TFSI)2.

[0061] According to an embodiment of the present application, the positive electrode sheet includes a positive electrode active material, a binder, a conductive agent and a current collector.

[0062] According to an embodiment of the present application, the positive electrode active material includes manganese-based, vanadium-based, Prussian blue and its analogs, organic materials, halogen-based materials and the like, wherein the positive electrode active material can be loaded onto the current collector by grinding and coating with a conductive agent and a binder.

[0063] According to an embodiment of the present application, the conductive agent includes at least one of conductive graphite, acetylene black, Super P, Ketjen black, carbon nanotubes, carbon fiber, metal fiber, graphene, etc., and the binder material includes at least one of PVDF, HSV, PTFE, CMC, SBR, SA, PAA, etc.

[0064] According to an embodiment of the present application, the positive electrode conductive current collector includes carbon felt, carbon paper, carbon cloth, stainless steel mesh, titanium mesh, stainless steel foil, titanium foil, etc.

[0065] According to the embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0066] According to an embodiment of the present application, the negative electrode plate includes a zinc metal plate, a foil material, a mesh material, and specifically includes a negative electrode active material, a conductive agent, a binder, and a current collector.

[0067] According to an embodiment of the present application, the negative electrode active material includes zinc powders with different particle sizes.

[0068] According to the embodiments of the present application, the materials of the conductive agent and the binder are consistent with those of the positive electrode.

[0069] According to an embodiment of the present application, the negative electrode conductive current collector includes metal copper, metal titanium, stainless steel, etc.

[0070] According to an embodiment of the present application, the membrane material includes at least one of the following: glass fiber, mixed cellulose ester, hydrophilic nylon, hydrophilic PVDF, polypropylene, etc.

[0071] According to the embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet are dispersed in a solvent to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0072] According to an embodiment of the present application, the zinc-based battery may include an outer package for packaging a positive electrode sheet, a negative electrode sheet, and an electrolyte.

[0073] According to an embodiment of the present application, the outer packaging may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.

[0074] According to an embodiment of the present application, the outer packaging of the zinc-based battery may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.

[0075] The outer packaging of the zinc-based battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0076] The zinc-based battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells may be assembled into a battery module, and the number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery modules may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0077] The second aspect of the present application provides a method for preparing the zinc-based battery described in the first aspect. According to an embodiment of the present application, the method comprises: coating a coating slurry on at least a portion of the surface of the positive electrode sheet and / or the separator, and drying to form the coating; wherein the coating slurry comprises the amphoteric hydroxide. The features and advantages described above for the zinc-based battery are also applicable to the method and will not be repeated here.

[0078] According to an embodiment of the present application, the coating slurry further includes at least one of a binder and an interface adsorbent and a solvent.

[0079] According to an embodiment of the present application, the solvent includes at least one of N-methylpyrrolidone, N-dimethylformamide, and deionized water. Thus, all coating components can be dissolved to form a uniform slurry, which helps to obtain a uniform coating.

[0080] According to an embodiment of the present application, the solid content of the coating slurry is 30% to 70% by mass, for example, 30%, 40%, 50%, 60%, or 70% by mass. Thus, the pH value of the electrolyte can be effectively buffered to avoid hydrogen precipitation and the generation of alkaline by-products, while suppressing water activity and further improving the stability of the electrolyte environment. In addition, the coating can stably adhere to the positive electrode sheet and / or the diaphragm, is not easy to fall off, has good affinity with the electrolyte, and is conducive to the transmission of electrons and ions. Thus, the overall electrochemical performance and cycle stability of the battery are better improved.

[0081] The third aspect of the present application provides an electrical device. According to an embodiment of the present application, the electrical device comprises the zinc-based battery described in the first aspect or the zinc-based battery obtained by the method for preparing the zinc-based battery described in the second aspect.

[0082] Battery cells, battery modules, and battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.

[0083] As an electrical device, a battery cell, battery module or battery pack can be selected according to its usage requirements.

[0084] As an embodiment, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0085] As another embodiment, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0086] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0087] Example 1

[0088] The components, relevant parameters and assembly process of the battery described in this example are as follows:

[0089] Positive electrode: Use β-MnO2 powder as active material, KS6 powder as conductive agent, and PVDF powder as binder. Weigh them in a mass ratio of 100:30:10, add solvent NMP until the solid content reaches 50%, and use a vacuum degassing machine to mix. The mixing time is 3 minutes and the speed is 4000 rpm. Take a stainless steel foil with a thickness of 0.1μm as the current collector, and use a 250μm scraper to coat the slurry at a coating speed of 1cm / s. Place the coated electrode in a 90℃ oven for 6 hours or more.

[0090] Coating: Use Al(OH)3 powder as the active material, PVDF powder as the binder, and sodium dodecylbenzene sulfonate (SDBS) as the interface adsorbent. After weighing at a mass ratio of 100:10:2, add solvent NMP until the solid content reaches 40%, and use a vacuum degassing machine for mixing. The mixing time is 3 minutes and the speed is 4000 rpm. Take the above-baked pole piece as the substrate, and use a 200μm scraper to coat the slurry at a coating speed of 1cm / s. Place the coated pole piece in a 90°C oven for 3 hours or more. Use a cutting machine to cut the dried pole piece into a circular pole piece with a diameter of 1.2cm.

[0091] Negative electrode: A commercial zinc sheet with a thickness of 0.1 μm was used and cut into a circular electrode with a diameter of 1.3 cm using a cutting machine.

[0092] Battery assembly: Use the above pole pieces as positive pole pieces and negative pole pieces respectively, and 2mol / L MnSO4+1mol / LZnSO4 as electrolyte. Use CR2032 button battery device for assembly, and use glass fiber diaphragm for diaphragm. Place the positive electrode shell, positive pole piece, diaphragm, electrolyte, negative pole piece, gasket, shrapnel, and negative electrode shell in order, and use automatic button packaging machine for packaging. Among them, the amount of electrolyte used is 100μL, and the diameter of the circular diaphragm is 1.6cm. The design pressure of the packaging machine is 650kg, and the design packaging time is 2s.

[0093] The differences between Examples 2-21, Comparative Examples 1-4 and Example 1 are shown in Table 1.

[0094] Cyclic performance test

[0095] In order to illustrate the improvement of battery performance by the insoluble amphoteric hydroxide coating, the batteries prepared in Examples 1-21 and Comparative Examples 1-4 were subjected to electrochemical performance tests, and the test method was as follows:

[0096] The Wuhan Blue Electric electrochemical test cabinet was used for charge and discharge tests. The current parameter was set to 0.5C according to the amount of active material, so that the charge and discharge time reached 2h respectively. The cut-off voltage was 1.8V during charging, 0.4V during discharging, and the number of cycles was set to 1000. The actual number of cycles was determined based on the performance. Among them, the point-taking method is to take a point every 20mV or 30s, and the voltage / current specifications of the test cabinet must be higher than the actual voltage / set current. After the test, the actual discharge specific capacity during the cycle was calculated, and the average discharge capacity of the first fifty cycles was used as the benchmark 0%. The specific capacity in the range of (0-30)% to (0+30)% belongs to the stable discharge cycle, and the total number of cycles is the stable discharge cycle. The test results are shown in Table 1.

[0097] Table 1

[0098]

[0099]

[0100] Since the definition of the number of stable cycles is related to the discharge specific capacity in the cycle, the length of the number of cycles can reflect the stability of subsequent cycles. When the overall capacity is significantly attenuated, the battery is judged to be failed.

[0101] As shown in Table 1, compared with Comparative Examples 1-3, Examples 1-21 using zinc-based batteries with coatings containing amphoteric hydroxides all have higher average discharge specific capacity and stable discharge cycles, indicating that after the introduction of the amphoteric coating, the electrode-electrolyte interface will be regulated by the coating main material for the interface ion concentration, creating a more stable electrochemical reaction environment, thereby improving the overall cycle stability. Comparative Example 4 uses tin sulfide in amphoteric sulfides, which has weaker ability to regulate acidity and alkalinity, and is inferior to amphoteric hydroxides in electrochemical performance.

[0102] From the comparison between the data of Examples 1 and 2, 3 and 4, and 5 and 6, it can be seen that the position of the coating has a certain influence on the battery performance. Compared with the coating located on the diaphragm, when the coating is located on the positive electrode sheet, the contact between it and the positive electrode is closer, the electron or ion conduction path is shortened, and the average discharge specific capacity is higher. When the coating is set on the diaphragm, it can radiate to the negative electrode interface to a certain extent, so the stability is slightly improved.

[0103] From the data of Examples 1-6, it can be seen that there are certain differences between different types of insoluble amphoteric hydroxides, which are related to the properties of the compounds themselves. For example, zinc hydroxide has better compatibility with zinc-based batteries, so the number of stable cycles is improved, while aluminum hydroxide and beryllium hydroxide have stronger ion regulation capabilities, so the average discharge specific capacity is higher.

[0104] From the data of Examples 1, 14-16, it can be seen that the use of binders and interface adsorbents in the coating can also help improve the discharge capacity and stability. Among them, the binder mainly acts on the stability of the coating structure, so it has a significant effect on the cycle stability; the interface adsorbent promotes the interface wetting efficiency to improve the activation rate of the system, which has a significant effect on the discharge capacity.

[0105] It can be seen from the data of Examples 1 and 17 that when the proportion of amphoteric hydroxides in the coating is low, due to the weakened contact with the electrolyte, the pH buffering capacity and the ability to inhibit water activity are reduced, which will simultaneously affect the specific capacity and cycle stability.

[0106] It can be seen from the data of Examples 1 and 18 that when the proportion of interfacial adsorbent in the coating is too high, the specific capacity or stability cannot be further improved. Instead, it will occupy the contact sites of the amphoteric hydroxide, causing a slight decrease in performance.

[0107] It can be seen from the data of Examples 1 and 19 that when the proportion of binder in the coating is too high, the performance also decreases. This is because the binder is generally a long-chain structure, and when the content is too high, it is not conducive to dispersion, resulting in a decrease in the contact site amount of the amphoteric hydroxide.

[0108] It can be seen from the data of Examples 1, 20 and 21 that if the coating thickness is too high, it will not help to improve the performance, but will increase the cost and occupy more volume; if the coating thickness is too low, the total amount of amphoteric hydroxide will be reduced, the overall regulation ability will be weakened, and the performance will be reduced.

[0109] Embodiment 22

[0110] The difference between Example 22 and Example 1 is that the battery assembly form is changed from a button battery to a beaker battery. The specific assembly steps are as follows:

[0111] The beaker battery device was used for assembly. The positive electrode and the negative electrode were clamped with platinum clips, and the relative area of ​​the positive electrode and the negative electrode immersed in the electrolyte was 1 cm. 2 .

[0112] Comparative Example 5

[0113] Comparative Example 5 differs from Example 22 in that it does not contain a coating.

[0114] Run pH measurement

[0115] In order to illustrate the stabilizing effect of insoluble amphoteric hydroxides on the pH environment of the electrolyte, Example 22 and Comparative Example 5 were subjected to pH measurement. The test method and data analysis are as follows:

[0116] The pH value of the electrolyte in the initial state and after each cycle of discharge was measured using a Shanghai Leici PHS-3E benchtop pH meter. Before testing the pH, calibration was performed using a pH buffer. The charge and discharge cycles were performed using a Wuhan Blue Electric electrochemical test cabinet. The current parameter was set to 0.1C based on the amount of active material, the cutoff voltage was 1.8V during charging, and the cutoff voltage was 0.4V during discharging. The test results are as follows: Figure 1 shown.

[0117] By comparing the two curves, it can be seen that the pH value of Example 11 is stable at around 4.3 from the initial stage to the subsequent stage, without obvious fluctuations; while Comparative Example 5 not only has a more drastic pH fluctuation in the early stage, but also the pH value reaches about 5 in the later stage, which is higher than Example 22. This shows that the amphoteric hydroxide coating can achieve a more effective pH buffering effect, and the overall pH is lower after use, which is more suitable for the current system.

[0118] Linear voltammetry test

[0119] In order to verify the inhibitory effect of insoluble amphoteric hydroxide on water activity, Example 1 and Comparative Example 1 were tested by linear voltammetry. The test method and data analysis are as follows:

[0120] The EC-lab electrochemical workstation was used to perform linear voltammetry tests, with open circuit voltage as the starting potential, 3.5V and -1V as the ending potential, and 1mV / s as the scan rate, for positive and negative scans, respectively. The test results are shown in Figure 2. Figure 2 , 3 shown.

[0121] like Figure 2 , 3 As shown, in the oxygen evolution stage caused by the positive scan, the overall peak current of the side reaction peak of Example 1 is small, and there is no obvious current disturbance after gas production; similarly, in the hydrogen evolution stage caused by the negative scan, the overpotential at the side reaction peak of Example 1 is larger, the peak current is smaller, and there is no test interruption caused by the current quickly reaching the safe current value. The smaller overpotential and larger peak current of Comparative Example 1 on the side reaction peak prove that it is more prone to corresponding side reactions, and the violent fluctuation of the current in the latter part of the scan further reflects that the stability of the system is lower than that of Example 1.

[0122] Since the magnitude of the current at the same potential is positively correlated with the reaction rate, and a larger overpotential indicates a higher difficulty in the reaction, it can be concluded that Example 1 using amphoteric hydroxides is less likely to cause side reactions such as hydrogen evolution and oxygen evolution than Comparative Example 1, which means a significant inhibition of water activity and a better maintenance of a stable electrolyte environment.

[0123] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A zinc-based battery, characterized in that: include: Positive electrode sheet, separator and negative electrode sheet; At least a portion of the surface of the positive electrode plate and / or at least a portion of the surface of the separator has a coating, and the coating includes an amphoteric hydroxide.

2. The zinc-based battery according to claim 1, characterized in that: The amphoteric hydroxide includes at least one of hydroxides of boron, aluminum, silicon, zinc, gallium, germanium, arsenic, selenium, indium, tin, antimony, tellurium, lead, bismuth, manganese, polonium and astatine.

3. The zinc-based battery according to claim 1 or 2, characterized in that: The amphoteric hydroxide includes at least one of Al(OH)3, Be(OH)2 and Zn(OH)2.

4. The zinc-based battery according to any one of claims 1 to 3, characterized in that: The mass percentage of the amphoteric hydroxide in the coating is 66% to 100%.

5. The zinc-based battery according to any one of claims 1 to 4, characterized in that: The coating further comprises: at least one of a binder and an interface adsorbent.

6. The zinc-based battery according to claim 5, characterized in that: The binder comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, styrene-acrylic acid and polyacrylic acid; And / or, the interfacial adsorbent includes anionic surfactant and / or nonionic surfactant.

7. The zinc-based battery according to claim 6, characterized in that: The anionic surfactant includes at least one of alkyl sulfates, sulfonates, fatty acids, fatty acid ester sulfates, carboxylic acid soap compounds and phosphate compounds; And / or, the nonionic surfactant includes at least one of polyoxyethylene alkylphenol ether and polyoxyethylene fatty alcohol ether.

8. The zinc-based battery according to any one of claims 1 to 7, characterized in that: The coating comprises: 60 to 100 parts by weight of amphoteric hydroxide; 0 to 20 parts by weight of a binder; 0 to 10 parts by weight of an interface adsorbent.

9. The zinc-based battery according to any one of claims 1 to 8, characterized in that: The coating has a thickness of 60 μm to 250 μm.

10. The zinc-based battery according to any one of claims 1 to 9, characterized in that: The positive electrode plate includes a positive electrode active material, and the positive electrode active material includes at least one of a manganese-based material, a vanadium-based material, Prussian blue and the like, a halogen-based material, and an organic material; And / or, the zinc-based battery further comprises: an electrolyte, wherein the electrolyte comprises water.

11. A method for preparing a zinc-based battery according to any one of claims 1 to 10, characterized in that: include: Applying a coating slurry on at least a portion of the surface of the positive electrode sheet and / or the separator, and drying to form the coating; Wherein, the coating slurry includes the amphoteric hydroxide.

12. The method according to claim 11, characterized in that The coating slurry further includes at least one of a binder and an interface adsorbent and a solvent.

13. The method according to claim 12, characterized in that The solvent includes at least one of N-methylpyrrolidone, N-dimethylformamide and deionized water.

14. The method according to any one of claims 11 to 13, characterized in that: The solid content of the coating slurry is 30% to 70% by mass.

15. An electrical equipment, characterized in that: A zinc-based battery comprising the zinc-based battery according to any one of claims 1 to 10 or a zinc-based battery obtained by the method for preparing the zinc-based battery according to any one of claims 11 to 14.

Citation Information

Patent Citations

  • Multifunctional composite diaphragm for high-stability aqueous zinc-based battery and preparation method of multifunctional composite diaphragm

    CN112103451A

  • Water-based lithium ion battery and preparation method thereof

    CN115882074A

  • Alkaline charging battery and method for making said charging battery

    CN1292579A

  • Nickel zinc battery

    WO2018078738A1